2016
DOI: 10.1002/art.39803
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Vitamin D Deficiency Is Associated With Endothelial Dysfunction and Increases Type I Interferon Gene Expression in a Murine Model of Systemic Lupus Erythematosus

Abstract: These findings indicate that vitamin D deficiency is associated with hampered vascular repair and reduced endothelial function, and may modulate type I interferon responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 16 publications
(21 reference statements)
1
18
0
Order By: Relevance
“…Ex vivo studies corroborated the possible vitamin D ability of positively enhancing the endothelial repair mechanisms and the global endothelial function [173,175], for example by reducing the NETosis [79]. Studies in experimental models of SLE (MRL/lpr) also showed that lower levels of vitamin D correlated with impaired endothelium-dependent vasodilation and defective neoangiogenesis in agreement with the human findings [176].…”
Section: Interventional Clinical Trialssupporting
confidence: 60%
“…Ex vivo studies corroborated the possible vitamin D ability of positively enhancing the endothelial repair mechanisms and the global endothelial function [173,175], for example by reducing the NETosis [79]. Studies in experimental models of SLE (MRL/lpr) also showed that lower levels of vitamin D correlated with impaired endothelium-dependent vasodilation and defective neoangiogenesis in agreement with the human findings [176].…”
Section: Interventional Clinical Trialssupporting
confidence: 60%
“…Whether these factors or their interactions will produce injury to the endothelium needs to be studied further in the future [ Table 1 ]. [ 65 66 67 68 69 70 ]…”
Section: R Isk F Actors R mentioning
confidence: 99%
“…Diseases of some other systems can be accompanied by endothelial injury, such as chronic obstructive pulmonary disease,[ 71 72 ] sepsis,[ 73 ] SLE,[ 70 ] obstructive sleep apnea,[ 74 ] end-stage renal disease,[ 75 ] left ventricular hypertrophy,[ 75 ] Blackfoot disease,[ 76 77 ] and type 2 diabetes[ 78 79 ] [ Table 1 ]. It may be that many diseases are connected to endothelial injuries to varying degrees, but uncovering those connections will require tireless scientific efforts.…”
Section: Oncurrency Of R Elated mentioning
confidence: 99%
“…Studies have shown that vascular endothelial structure and function damage was the initiating mechanism of atherosclerosis in SLE [ 4 , 5 ]. The essence of vascular dysfunction is the imbalance between vascular injury and vascular repair, which is an important factor leading to target organ damage, such as the heart, brain, and kidney damage, and cardiovascular events [ 6 , 7 ]. Therefore, the repair of vascular endothelial injury is an important measure to effectively prevent and treat SLE atherosclerosis and its complications.…”
Section: Introductionmentioning
confidence: 99%